Rainfall intensity plays an important role in the removal of PM from the leaf surfaces - Shijun Zhou (Elsevier, 2021)
Apparently, plant leaf surface particulate matter (PM) can be effectively removed by rainfall, leaving space on the leaf surface to adsorb and retain PM again. At present, most of the relevant studies adopt the method of artificial rainfall simulation to quantify rainfall characteristics in terms of rainfall intensity, and mostly focus on one category of plants. Studies of rainfall intensity on different categories of plants are lacking. Therefore, in this study, common urban greenery plants were classified into four categories, namely, trees, shrubs, herbs, and aquatic plants. Artificial rainfall was used and three different gradients of rainfall intensity, 30 mm/h, 45 mm/h and 60 mm/h, were set. The mass of per unit leaf area PM removal was calculated using the elution weighing method and the filter membrane method was used to classify the PM into three particle sizes: coarse (10–100-μm), fine (3–10-μm) and ultrafine (0.4–3-μm). It was devoted to investigating the differences in the effect of rainfall intensity on the removal of PM from the leaf surfaces of different categories of common urban greenery. The results showed that the removal of coarse particles by rainfall was the highest under different rainfall intensities. At the same time, the removal effects of rainfall on leaf surface PM of herbs were the highest under different rainfall intensity, while that of trees was the lowest. Among the same category of plants, Salix matsudana had better particle retention capacity among trees, Buxus sinica among shrubs, Poa pratensis among herbs, and Acorus calamus among aquatic plants. In addition, all tested plants had the highest mass of PM removed from leaf surface units at high rainfall intensity (60 mm/h). However, at a higher rainfall intensity (45 mm/h), the mass of PM on plant unit leaf surface removed was lower than the minimum rainfall intensity (30 mm/h). The results of the above study can provide a basis and theoretical support for the selection of species for urban green space restoration, as well as a reference for the establishment of urban cleaning systems from the perspective of the relationship between rainfall intensity and PM on plant leaf surfaces.